Influence of weed control methods on the yield and yield components of cowpea (Vigna unguiculata (L.) Walp.) varieties in Sokoto, Nigeria - J. Alhassan; A.I. Ukwetang (Journal of Applied Sciences and Environmental Management, 2022)
Field trial was carried out during the 2017 wet season (July to October) at the Dryland Teaching and Research Farm of the Faculty of Agriculture, Usmanu Danfodiyo University, Sokoto to determine the effect of weed control methods on the yield and yield components of three (3) cowpea (Vigna unguiculata (L.) Walp) varieties sourced from Sokoto Agricultural Development Project (SADP). Treatments consisted of factorial combination of four (4) weed control methods [Control (no weeding), Chemical weeding (Pendimethalin), Chemical + Hoe and Hoe weeding] and three (3) cowpea varieties [Dan Gidan Yunfa (Local), IT-288 and IT-277-2)]. Treatments were laid out in Randomized Complete Block Design (RCBD) replicated three (3) times. Data were collected on pod yield, grain yield, and haulm yield, total dry weight shelling percentage, 100-grain weight and weed dry weight. Dan Gidan Yunfa recorded higher pod and grain yield than the other varieties. Weed control had significant effect on weed dry matter, the control plot where no weeding was done throughout recorded the highest (103.50 kg ha-1, 114.32 kg ha-1, 139.45 kg ha-1) weed dry matter at 4, 8 and 12 WAS, respectively. Therefore, it could be concluded that Dan Gidan Yunfa performed better than other varieties in the study area. The pod and grain yield of the crop in the weeding treatments were not different from the control (no weeding).